DINAMIKA PENYEBARAN HOAKS DI MEDIA SOSIAL DAN EROSI KEPERCAYAAN PUBLIK DI INDONESIA - Kurniyawan, Ardi; Al Zaidan, Hilmi; Ramadhan, Rizky; Suryandari, Meity (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
When false claims spread faster than the corrections meant to counter them, societies face a genuine crisis of credibility. This study responds to the proliferation of hoax content across Indonesia's three dominant platforms TikTok, Instagram, and Twitter/X and its concrete effects on public confidence in key institutions. Employing descriptive qualitative methods and content analysis on 20 verified hoax posts from January 2025 to March 2026, the research identifies three distinct diffusion patterns: staged-exponential spread, cross-platform replication, and the recontextualization of authentic content. Health-themed hoaxes prove most prevalent (35%), followed by politically framed content (25%). The consequences reach beyond mere misinformation: measurable declines in public trust toward government bodies, medical professionals, and legacy media are documented. Viewed through the lens of Islamic Communication Studies, the tabayyun principle is reframed not simply as an ethical recommendation but as a contextually relevant cognitive protection mechanism for Indonesia's Muslim majority. The study's novelty lies in synthesizing technical-digital, social-institutional, and Islamic-ethical dimensions within a single analytical framework.